2021
DOI: 10.1051/e3sconf/202128505009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oil combinations on the structural properties of oleogels

Abstract: Studies of the effect of combinations of vegetable oils on the properties of oleogels will provide useful information from a technological viewpoint for the optimal choice of the composition of the oleogel used, as well as regulate the fatty acid composition of food products based on oleogels. This work aimed to study the effect of combinations of sunflower and linseed oils on the properties of oleogels structured with beeswax. As a result of the studies carried out, data were obtained on the change in the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
(12 reference statements)
1
5
1
Order By: Relevance
“…The crystals of these oleogels have an identical appearance, in contrast to the crystals formed in LO oleogels. LO oleogels form several types of crystals, predominantly spherulitic in shape, which agrees with the study [ 24 ]. In FO, SO- and OO-based oleogels with a concentration of 6 wt.% of the structure form a compact oleogel mesh ( Figure 1 A,C,D); due to the high concentration of beeswax, a high degree of oversaturation is provided, which accelerates the nucleation and subsequent gelation.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The crystals of these oleogels have an identical appearance, in contrast to the crystals formed in LO oleogels. LO oleogels form several types of crystals, predominantly spherulitic in shape, which agrees with the study [ 24 ]. In FO, SO- and OO-based oleogels with a concentration of 6 wt.% of the structure form a compact oleogel mesh ( Figure 1 A,C,D); due to the high concentration of beeswax, a high degree of oversaturation is provided, which accelerates the nucleation and subsequent gelation.…”
Section: Resultssupporting
confidence: 92%
“…LO-based oleogels were found to have the lowest oil-binding capacity (less than 70%), which may be related to the spherulitic crystal shape, which, according to [ 27 ], is not favorable for the retention of large amounts of oil. However, this contradicts the study [ 24 ], where the linseed oil-based oleogels exhibited an OBC of around 90%. According to [ 32 ], when varying the ratio of individual components in the oleogels, the values of oil loss can undergo significant changes.…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…In contrast, the addition of 42%, 45%, and 48% oil increased these parameters (p < 0.05). Hence, the obtained analysis showed that oil concentration influenced the hydrogel texture parameters [11,12]. The analysis of the rheological parameters of the hydrogel with encapsulated safflower oil are shown in Table 2.…”
Section: Texture and Rheological Analysismentioning
confidence: 89%
“…The composition of oleogels is often diverse and can vary both in the dispersion medium [ 15 , 16 , 17 ] and the dispersed phase [ 18 , 19 ], which in turn affects the final properties of the oleogels. Usually, canola oil [ 19 ], sunflower or linseed oil [ 16 , 20 ], and fish oil [ 21 ] are used as dispersion mediums. The use of different oils, including their combinations, allows for the regulation of the fatty acid composition of both oleogels and the products containing them.…”
Section: Oleogels In Food Productsmentioning
confidence: 99%